"Evaluación química y biológica de la fertilidad de un suelo desarrollado sobre andesita en el sector San Vicente de la parroquia Chuqiribamba, cantón Loja". - Aguirre Vásquez, Valeria Stefania (2017)
In San Vicente area, located in Chuquiribamba-Loja district, the application of fertilizers without considering the availability of nutrients in the soil and the lack of it´s restitution extracted from maize, strawberry and vegetable crops. Result in low yields and low soil fertility. With these precedents, it was proposed to provide information on the availability of nutrients, which are the limiting fact to the correct development of crops, because the chemical analyzes carried out in the country's soil laboratories, to assess the availability of nutrients, do not always reflect with veracity the quantity of the element. The contents of N, P, K, S, Mg, Fe, Mn, Cu, Zn and B, were chemically analyzed (Modified Olsen) and biological evaluation were evaluated using the missing element method, establishing a correspondence between the two methods. In the six soil uses identified in the site, the physical conditions of the soil in the layer of 00-25 cm were placed in the category of very poor. The soil reaction (pH H2O) was characterized from very acid to practically neutral, the cation exchange capacity (C.I.C.) was in the high range; the adding of total bases (K +, Ca +, Mg+) was found in the middle range. In the biological evaluation both plant height and dry biomass, it was shown that N and P are the most deficient followed by K, whereas Cu, Mg, S, Mn, Fe, Zn and B were found in a medium range. The correlation between dry biomass and the available soil chemical analysis was: elevated for Cu, P and Mg (r = 0.86, 0.85 and 0.83, respectively), in a moderate proportion for the elements of K, Zn and N (r = 0.78, 0.67 and 0.54, respectively); Low for Fe and S (r = 0.43 and 0.48, respectively). Key words: biological evaluation, Modified Olsen extraction, nutrient solutions, indicator plant, correlation.